2007
DOI: 10.1002/smll.200700250
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid of Ultralong Carbon Nanotubes

Abstract: The long and short of it: An ionic liquid with good thermal stability can be prepared from 100–500‐nm‐long multi‐walled carbon nanotubes (MCNTs). The MCNTs are functionalized with a polysiloxane quaternary ammonium compound followed by a sulfonate salt. A coating of average thickness 6.5 nm comprising an ionic bilayer structure perpendicular to the nanotube surface is obtained (see TEM image).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…Figure 6A,B shows TEM images of CaCO3 NFs. The figure shows that the CaCO3 NF's surface was wrapped in a shell structure formed by organic matter, and the thickness of the shell was about 5.6 nm, which was close to the theoretically calculated thickness of organic matter layer 5.9 ± 0.4 nm [39]. It was reported that this organic matter layer provided CaCO3 NPs with cohesive and slip-like properties that acted as a "solvent phase" in the system, giving the system a certain viscosity and Figure 5A, the CaCO 3 NPs' shape was cubic, and the particle size was about 50 nm.…”
Section: Low-temperature Creep Propertiessupporting
confidence: 85%
“…Figure 6A,B shows TEM images of CaCO3 NFs. The figure shows that the CaCO3 NF's surface was wrapped in a shell structure formed by organic matter, and the thickness of the shell was about 5.6 nm, which was close to the theoretically calculated thickness of organic matter layer 5.9 ± 0.4 nm [39]. It was reported that this organic matter layer provided CaCO3 NPs with cohesive and slip-like properties that acted as a "solvent phase" in the system, giving the system a certain viscosity and Figure 5A, the CaCO 3 NPs' shape was cubic, and the particle size was about 50 nm.…”
Section: Low-temperature Creep Propertiessupporting
confidence: 85%
“…In sharp contrast, the previous hybrid self-suspended NPs that flow exhibit liquid-like rheological behavior. [1][2][3][4][5][6][7][8][9][10] Both G' and G'' decrease with increasing temperature.…”
mentioning
confidence: 99%
“…Various hybrid self-suspended NPs have been synthesized from surface modification of the nanostructures, for example, SiO 2 , g-Fe 2 O 3 , [1,2] TiO 2 , [3] ZnO, [4] quantum dots, [5] gold, platinum, palladium, [6] CaCO 3 , [7] and carbon nanotubes. [8][9][10] The intrinsic electronic, magnetic, and luminescent properties of various nanostructures have made the self-suspended NPs a promising alternative to conducting lubricants, heat-transfer fluids, batteries, and printing electronics. [2,4,11] Aside from the above mentioned self-suspended NPs and their corresponding liquid-like [1,2] behavior, herein we report a self-suspended polyaniline (PANI) that exhibits a unique thermoreversible gel-like rheological response.…”
mentioning
confidence: 99%
“…Recently, Giannelis and co‐workers4 pioneered a new class of hybrids, termed nanoparticle ionic materials (NIMs), which comprise a nanoparticle core functionalized with a covalently tethered ionic corona. Solvent‐free CaCO 3 ,5 protein,6 and carbon nanotube7 liquids adopting this approach have been reported. In these sorts of NIMs, a cationic oligomeric corona is grafted onto the nanoparticle cores, and anionic surfactants act as a counterion to produce solvent‐free nanoparticle ionic liquids 8.…”
Section: Methodsmentioning
confidence: 99%